2011
DOI: 10.1128/aac.01585-10
|View full text |Cite
|
Sign up to set email alerts
|

NDM-1-Producing Escherichia coli in Germany

Abstract: ᰔThe bla NDM-1 carbapenemase gene has now been identified among many different enterobacterial species from many countries (1,7,(10)(11)(12)(13)(14). Its current spread has often been associated with importations from the Indian subcontinent.Here we report the case of a 70-year-old man admitted to the intensive care unit of a hospital in Bonn, Germany, in December 2009. This patient had been hospitalized in India 3 months before as a consequence of a trauma that made him paraplegic. An acute appendicitis assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 12 publications
0
29
0
2
Order By: Relevance
“…Sequence analysis of the seven housekeeping genes selected for multilocus sequence typing (MLST) (45) showed that E. coli 271 belongs to the MLST ST101 and is therefore classified in the phylogenetic subgroup B1 that corresponds to a commensal strain. It is noteworthy that two other ST101-type E. coli isolates producing NDM-1 have been recently identified in Germany and Canada (32,33), with a link with the Indian subcontinent in both cases. In contrast, the community-acquired E. coli GUE that had been recovered from a French woman who was living in India and that coexpressed NDM-1 and CTX-M-15 belonged to the ST131 type (6,37).…”
Section: Resultsmentioning
confidence: 99%
“…Sequence analysis of the seven housekeeping genes selected for multilocus sequence typing (MLST) (45) showed that E. coli 271 belongs to the MLST ST101 and is therefore classified in the phylogenetic subgroup B1 that corresponds to a commensal strain. It is noteworthy that two other ST101-type E. coli isolates producing NDM-1 have been recently identified in Germany and Canada (32,33), with a link with the Indian subcontinent in both cases. In contrast, the community-acquired E. coli GUE that had been recovered from a French woman who was living in India and that coexpressed NDM-1 and CTX-M-15 belonged to the ST131 type (6,37).…”
Section: Resultsmentioning
confidence: 99%
“…It is the most recently discovered carbapenemase that is spreading rapidly worldwide (13,15,17,31). NDM-1 producers have been identified mainly in the United Kingdom, India, and Pakistan (9), but numerous studies within the last year reported NDM-1 producers from many countries in Europe (18,22,25), Asia, Africa, Australia, and North America (4,6,16,23). Most of the patients infected by NDM-1 producers are from India, Pakistan, or Bangladesh or have traveled in the Indian subcontinent.…”
mentioning
confidence: 99%
“…The subsequent worldwide reports on the emergence of blaNDM-1 producing bacteria clearly showed the role of plasmid vectors in their dissemination as they were found to be residents on large plasmids. Occurrence of blaNDM-1 producing E. coli from patients with a history of previous hospitalization in India was first reported in 2011 from Germany [30]. Nielsen et al, 2012, reported that an NDM-1 producing E. coli obtained in Denmark has a genetic profile similar to an NDM-1 producing E. coli isolate from UK, suggesting dissemination of a common plasmid into various sequence types of E. coli [31].…”
Section: Discussionmentioning
confidence: 99%